Wideband millimeter wave rectangular dielectric resonator antenna for 5G applications - Abinash Gaya; Mohd Haizal Jamaluddin; Irfan Ali (Institute of Advanced Engineering and Science, 2020)
A probe fed rectangular dielectric resonator antenna (DRA) is designed here for millimeter wave 5G applications. A wide bandwidth of 5GHz has been achieved with frequency range from 24.24GHz to 29. 20GHz. The calculated percentage banwidth is 19% centered at 26GHz. The DRA is fed by a probe with a microstrip line of unequal strip dimensions over the substrate. The measured gain of the antenna is 6.25dBi. The calculated radiation efficiency is 96%. The measured axial ratio bandwidth is from 24.08GHz to 23.90GHz, which is about 0.75 percentage bandwidth. The probe height above to the substrate is optimized to exite the DRA. The microstripline coupling is used to resonate the DRA at desizred resonating frequency. The widebandwidth with high efficiency achived here will make this antenna suitable for the 5G applications at band 30 GHz.